Peptídeo-conjugados derivados da toxina ParE: design, síntese e estudos biológicos - Bedoya, Jose Gregorio Martin [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O desenvolvimento de novos fármacos com ação antibacteriana e antitumoral requer a identificação de um alvo celular específico. Um grupo de moléculas que se tornou alvo celular efetivo para agentes terapêuticos é o das topoisomerases. As topoisomerases, são enzimas essenciais para os processos de replicação e transcrição do DNA e, portanto, para a viabilidade celular. Inúmeros agentes antibacterianos atuam inibindo a atividade destas enzimas, como as quinolonas, cumarinas, microcinas e toxinas bacterianas, tais como ParE e CcdB. ParE inibe a síntese de DNA agindo diretamente na ação de duas topoisomerases: DNA girase e topoisomerase IV. Peptídeos derivados de ParE têm sido descritos como inibidores de topoisomerases bacterianas in vitro e, portanto, agentes antibacterianos em potencial. No entanto, a baixa capacidade destes peptídeos em permear a membrana plasmática bacteriana impede o uso dos mesmos para fins terapêuticos. Para contornar esta limitação, decidiu-se neste trabalho, projetar e sintetizar peptídeo-derivados de ParE, conjugados com fluoroquinolonas e moléculas contendo grupos cumarínicos, e avaliar a capacidade de inibir a atividade de diferentes topoisomerases bem como, em prevenir o crescimento bacteriano. Para isso, peptídeo-conjugados foram sintetizados pela metodologia de fase sólida, purificados e analisados por cromatografia líquida de alta eficiência e caracterizados por espectrometria de massas. Análise de dicroísmo circular revelou uma conformação predominante em folha-β nos peptídeos, e que as conjugações em ParELC3M não alteraram de forma significativa sua estruturação secundária. A capacidade de inibição destes compostos sobre a atividade das topoisomerases foi testada por ensaios de eletroforese em gel. Atividades antibacteriana e antifúngica avaliadas pelo método de microdiluição em caldo e a viabilidade celular pelo método de MTT. Um peptídeo derivado de ParE (ParELC3M) e seus conjugados CFX-ParELC3M, CICPOQ-ParELC3M, HOCAc-ParELC3M e CFXPip-ParELC3M foram obtidos e testados. Tentativa de expressão da proteína ParE também foi realizada, objetivando a obtenção da toxina para estudos comparativos. Em ensaios padrão de superenrolamento e relaxamento do DNA, o peptídeo ParELC3M e seus conjugados, não inibiram completamente a atividade da DNA girase de E. coli e S. pneumoniae, mas inibiram a DNA girase de M. tuberculosis em concentrações entre 50 e 12,5 µmol.L-1. Por outro lado, todos peptídeo-conjugados inibiram a reação de relaxamento catalisada pelo topo IV de E. coli e S. pneumoniae com valores de IC100 entre 50 e 25 µmol.L-1. Adicionalmente, os peptídeo-conjugados CFX-ParELC3M e CFXPip-ParELC3M inibiram a topo IA de E. coli e Topo II de levedura com valores de IC100 menores que 6,25 µmol.L-1 e 3,125 µmol.L-1, respectivamente. Somente CFXPip-ParELC3M foi capaz de inibir o crescimento bacteriano, com um valor de MIC de 25 µmol.L-1. Mas em relação à atividade antifúngica, os peptídeos-conjugados não apresentaram inibição de crescimento de C. albicans. Estes resultados indicam que a conjugação de grupos fluoquinolônicos a peptídeos inibidores de topoisomerases, tal como ParELC3M, podem facilitar sua passagem através da membrana bacteriana para atingir seu alvo intracelular, as topoisomerases. Além disso, os peptídeo-conjugados não demostraram toxicidade em células MRC-5. Os resultados indicam que os conjugados derivados de ParE representam uma estratégia promissora para o desenvolvimento de novos agentes antimicrobianos.

The development of new drugs with antibacterial and antitumor action requires the identification of a specific cellular target. A group of molecules that has become an effective cellular target for therapeutic agents is the topoisomerases. Topoisomerases are enzymes essential for DNA replication and transcription processes, and therefore for cell viability. Numerous antibacterial agents act by inhibiting the activity of these enzymes, such as quinolones, coumarins, microcins, and bacterial toxins such as ParE and CcdB. ParE inhibits DNA synthesis by directly targeting the action of two topoisomerases: DNA gyrase and topoisomerase IV. Peptides derived from ParE have been described as inhibitors of bacterial topoisomerases in vitro and, therefore, potential antibacterial agents. However, the low capacity of these peptides to penetrate the bacterial plasma membrane prevents their use for therapeutic purposes. To circumvent this limitation, it was decided in this work, to design and synthesize peptide derivatives of ParE, conjugated with fluoroquinolones and molecules containing coumarin groups, and to evaluate their ability to inhibit the activity of different topoisomerases as well as to prevent bacterial growth. Therefore, peptide-conjugates were synthesized using solid-phase methodology, purified, and analyzed by high-performance liquid chromatography, and characterized by mass spectrometry. Circular dichroism analyses revealed a predominant β-sheet conformation in the peptide, and that the conjugations did not significantly alter their secondary structure. The inhibitory capacity of these compounds on topoisomerases activity was tested by gel electrophoresis assays. Antibacterial and antifungal activity were evaluated by broth microdilution method, and cell viability by MTT method. A peptide derived from ParE (ParELC3M) and its conjugates CFX-ParELC3M, CICPOQ-ParELC3M, HOCAc-ParELC3M, and CFXPip-ParELC3M were obtained and tested. Attempted expression of the ParE protein was also performed, aiming to obtain the toxin for comparative studies. In standard DNA supercoiling and relaxation assays, the ParELC3M peptide and its conjugates did not completely inhibit the activity of E. coli and S. pneumoniae DNA gyrase, but inhibited M. tuberculosis DNA gyrase at concentrations ranging 50 µmol.L-1 to 12.5 µmol.L-1. On the other hand, all peptide-conjugates inhibited the relaxation reaction catalyzed by E. coli and S. pneumoniae topoisomerase IV with IC100 values ranging from 50 to 25 µmol.L-1. Additionally, the peptide-conjugates CFX-ParELC3M and CFXPip-ParELC3M inhibited E. coli topoisomerase IA and yeast Topo II with IC100 values lower than 6.25 µmol.L-1 and 3.125 µmol.L-1, respectively. Only CFXPip-ParELC3M was able to inhibit bacterial growth, with an MIC value of 25 µmol.L-1. However, regarding antifungal activity, the peptide-conjugates showed no inhibition against C. albicans. These results indicate that conjugating fluoroquinolone groups to topoisomerase inhibitor peptides, such as ParELC3M, may facilitate their passage through the bacterial membrane to reach their intracellular target, the topoisomerases. Additionally, the peptide-conjugates showed no toxicity in MRC-5 cells. The results suggest that conjugates derived from ParE represent a promising strategy for the development of new antimicrobial agents.
Peptide-conjugates derived from ParE toxin: design, synthesis, and biological studies
Keywords: Peptídeos; DNA polimerases; Antimicrobianos; Toxinas bacteriana; Antitoxinas; Peptides; DNA polymerases; Antimicrobials; Bacterial toxins; Antitoxins